the aesthetics of Omani portraiture using stencil and silkscreen styles among students of the Art Education Department at Sultan Qaboos University (Al-Academy, 2024)
The art of portraits is considered one of the most prominent branches of the visual arts that is rich in expressive creativity, and one of the most indicative of the features of national identity, whether through facial expressions, or through the association of some features with distinct ethnic characteristics with the cultural and popular heritage of a particular civilizational composition. As well as fashion and ornamental styles that complement the portrait.        In addition to the impact of the aforementioned considerations in enriching the ideas of portrait artists, and providing them with a visual repertoire that is capable of countless manipulations and formulations that are open to all trends, artistic styles, and technical performances, in various fields of art, they also represent important sources for re-examining the features of environmental and cultural identity and ethnicity with its associated symbols and connotations. Therefore, approaching the art of portraiture from this angle was a study capable of revealing some of the most important motives that lead artists to be inspired by topics and ideas closely related to the art of the portrait, as well as to clarify the ways in which these works would include within them values ​​that go beyond the apparent aesthetic level, to a level deeper is related to the concept of identity as a general framework for each culture with its own particularity.        This research focuses mainly on portrait works carried out using some printmaking media. It aims to approach some of the most prominent aesthetic characteristics of contemporary portrait art in the Sultanate of Oman - which researchers use the term (Omani portraiture) to refer to in the research - through analyzing a group of printmaking artworks, produced by a number of students from the Department of Art Education at Sultan Qaboos University in the graphics course